(untitled) (Semiárida, 2025)
The objective of this study was to apply and evaluate techniques to improve the quality of photographic images of weeds in their early phenological stages, given that their development competes with horticultural crops. The methodology consisted of field trips in different seasons of the year, in fruit and vegetable crop plots in the Lower Río Negro Valley (VIRN). Plant individuals in their cotyledonary stage were selected and prepared by clearing the environment, homogenizing the soil, and controlling natural light using reflective and diffusing screens. Photographs were taken with cell phones and a semi-professional camera in high resolution in JPG and HEIC formats for later editing. The results show that the application of simple strategies such as the use of a black background, soil homogenization, appropriate lighting selection, and the elimination of extraneous elements significantly improved image quality. Furthermore, the use of Photopea software allowed for the optimization of parameters such as brightness, contrast, and white balance while maintaining the visual fidelity of the specimens. The images obtained are suitable for use in educational materials and botanical identification. It is concluded that the combination of photographic, environmental, and digital editing techniques allows for the production of high-quality images that accurately capture the distinctive features of plants. These practices are especially useful for the development of plant recognition manuals and can be extended to other areas of biological and agricultural sciences, improving visual documentation in the early stages of plant development.